Photodegradation of Eosin Y Using Silver-Doped Magnetic Nanoparticles - Eman Alzahrani (International Journal of Analytical Chemistry)
The purification of industrial wastewater from dyes is becoming increasingly important since they are toxic or carcinogenic to human beings. Nanomaterials have been receiving significant attention due to their unique physical and chemical properties compared with their larger-size counterparts. The aim of the present investigation was to fabricate magnetic nanoparticles (MNPs) using a coprecipitation method, followed by coating with silver (Ag) in order to enhance the photocatalytic activity of the MNPs by loading metal onto them. The fabricated magnetic nanoparticles coated with Ag were characterised using different instruments such as a scanning electron microscope (SEM), transmission electron microscopy (TEM), energy-dispersive X-ray (EDAX) spectroscopy, and X-ray diffraction (XRD) analysis. The average size of the magnetic nanoparticles had a mean diameter of about 48 nm, and the average particle size changed to 55 nm after doping. The fabricated Ag-doped magnetic nanoparticles were used for the degradation of eosin Y under UV-lamp irradiation. The experimental results revealed that the use of fabricated magnetic nanoparticles coated with Ag can be considered as reliable methods for the removal of eosin Y since the slope of evaluation of pseudo-first-order rate constant from the slope of the plot between ln⁡(Co/C) and the irradiation time was found to be linear. Ag-Fe3O4 nanoparticles would be considered an efficient photocatalyst to degrade textile dyes avoiding the tedious filtration step.